The Medical Life of Henry Norman Bethune - Jean Deslauriers; Denis Goulet (Canadian Respiratory Journal)
BACKGROUND: Henry Norman Bethune is one of the most exciting and incredible surgeons that Canada has ever produced. Indeed, he is often characterized as one of the world’s best-known surgeons. He was an innovator and his scientific contributions have stood the test of time. In Canada, he will forever be remembered as a social activist committed to the welfare of the poor and to the reform of the health care system. In the People’s Republic of China, he is idolized and remains the only foreigner to ever become a national hero.